2006
DOI: 10.1002/jcc.20421
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio potential energy surface and predicted microwave spectra for ArOCS dimer and structures of ArnOCS (n = 2–14) clusters

Abstract: An ab initio potential energy surface for the Ar--OCS dimer was calculated using the coupled-cluster singles and doubles with noniterative inclusion of connected triples [CCSD(T)] with a large basis set containing bond functions. The interaction energies were obtained by the supermolecular approach with the full counterpoise correction for the basis set superposition error. The CCSD(T) potential was found to have two minima corresponding to the T-shaped and the collinear Ar--SCO structures. The two-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In deciding which combination to use we are aided once again by previous ab initio calculations on atom-OCS complexes, in which ͗R͘, ͗͘, and calculated rotational constants are presented. 30,39,40 Examining HeOCS, NeOCS, and ArOCS shows that R values determined using A , C or B , C are within ϳ0.01 Å of ͗R͘, while taking the average of the three values gives the best estimate of ͗͘, lying within 0.1°for NeOCS and ArOCS and within 0.5°for HeOCS. Thus, we use A , C or B , C to determine R, and the average from the three combinations to determine .…”
Section: Discussionmentioning
confidence: 95%
“…In deciding which combination to use we are aided once again by previous ab initio calculations on atom-OCS complexes, in which ͗R͘, ͗͘, and calculated rotational constants are presented. 30,39,40 Examining HeOCS, NeOCS, and ArOCS shows that R values determined using A , C or B , C are within ϳ0.01 Å of ͗R͘, while taking the average of the three values gives the best estimate of ͗͘, lying within 0.1°for NeOCS and ArOCS and within 0.5°for HeOCS. Thus, we use A , C or B , C to determine R, and the average from the three combinations to determine .…”
Section: Discussionmentioning
confidence: 95%
“…4 Species such as CO 2 , OCS, N 2 O, and CS 2 belong to a class and have similar properties, due to their isovalent electrons. Except for Rg-CS 2 (Rg = He, Ne, Ar, Kr, and Xe) complexes, the complexes consisting of such species (CO 2 , a) Electronic addresses: zhenglimin@wipm.ac.cn; cxduan@phy.ccnu.edu.cn; yplu@ntu.edu.sg OCS, N 2 O) and rare gas atoms have received much attention in both experimental [5][6][7][8][9][10][11][12] and theoretical studies, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] due to their fundamental nature and practical importance. In experiment, the microwave and infrared spectra for these complexes were reported widely [8][9][10][11][12] and showed that each complex has a T-shaped structure.…”
Section: Introductionmentioning
confidence: 99%
“…In theoretical calculations, many ab initio potential energy surfaces for these complexes have been available in literatures. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Very similar features are found on their PESs, such as the global "T-shaped" minimum, local linear minima, and saddle points. The intermolecular interactions in these complexes vary systematically with both the polarizability of the rare gas atoms and with the electronic structures of the linear molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Because of symmetry given by Equation (12), only even values of n and l are acceptable physically in the long-range part of potential energy and in this work, X = cos 2 (θ ) is used in the short-range part of potential energy surface in this work although, in other works [8,14,16] X = cos (θ ) is used.…”
Section: Analytical Representation Of the Intermolecular Potential Enmentioning
confidence: 97%